2018
DOI: 10.7150/jca.23805
|View full text |Cite
|
Sign up to set email alerts
|

Association between the SNPs of the TOB1 gene and gastric cancer risk in the Chinese Han population of northeast China

Abstract: The TOB1 (ErbB-2,1) gene is an anti-proliferative factor that has the potential to regulate cell growth and encodes a member of the transducer of erbB-2/B-cell translocation gene protein. The association between the polymorphisms of the TOB1 gene and gastric cancer (GC) risk is still unclear. In this study, 506 GC cases and 548 healthy controls (HCs) were collected to evaluate the association between the eleven SNPs (rs35220381, rs12950561, rs7221352, rs61482741, rs9303568, rs34700818, rs12949115, rs9903822, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Both effects involve complex regulatory networks, such as those mediated by p53, PI3K/AKT/mTOR, Ras, and microRNA ( Zhou et al, 2016 ). Our group has demonstrated that TOB1 is a tumor suppressor in gastric cancer ( Guan et al, 2017 ; Guo et al, 2019 ; Wang et al, 2019 ; Wang et al, 2018 ; Yu et al, 2011 ; Yu et al, 2008a ; Yu et al, 2008b ). Experimental data from our study indicated that TOB1 may induce autophagy in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Both effects involve complex regulatory networks, such as those mediated by p53, PI3K/AKT/mTOR, Ras, and microRNA ( Zhou et al, 2016 ). Our group has demonstrated that TOB1 is a tumor suppressor in gastric cancer ( Guan et al, 2017 ; Guo et al, 2019 ; Wang et al, 2019 ; Wang et al, 2018 ; Yu et al, 2011 ; Yu et al, 2008a ; Yu et al, 2008b ). Experimental data from our study indicated that TOB1 may induce autophagy in gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The candidate SNPs were selected using the dbSNP database ( http://www.ncbi.nlm.nih.gov/snp ) and the 1000 Genomes database ( https://www.ncbi.nlm.nih.gov/variation/tools/1000genomes/ ). These SNPs were selected based on the criterion of the minor allele frequency (MAF) greater than 0.05 in the Chinese Han population [ 21 ]. Ultimately, six SNPs (rs7240736, rs73937194, rs3817466, rs8082898, rs73381527 and rs9953490) of DAL-1 gene met the requirement and were included in our study in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Continuous variables with a normal distribution were described as mean ± SD and compared with the Student’s t-test [ 21 ]. Discrete variables we re described as frequency (percentage) and compared using the Chi-square (χ 2 ) test [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations